The Development of Artificial Intelligence Technology and Cyber Security Threats - Siti Sa’adah; Yulianah Yulianah; Neysha Putri Vaquitasari; Eka Septiana; Rafi Rasidin; Wanda Laksniyunita (Advances in Community Services Research, 2026)
Purpose: This study aims to examine the relationship between advances in Artificial Intelligence (AI) and the evolving cybersecurity landscape by identifying emerging AI-enabled threats, exploring AI-based defense mechanisms, and analyzing the challenges of implementing AI-driven cybersecurity systems. Research Method: A structured literature review using a qualitative descriptive approach was conducted. Relevant studies published between 2021 and 2025 were systematically identified through major academic databases using predefined search keywords. The selected studies were screened using inclusion and exclusion criteria and analyzed through thematic content analysis. Results and Discussion: The findings indicate that AI simultaneously functions as a catalyst for increasingly sophisticated cyber threats and as an enabler of advanced cybersecurity defenses. Three dominant themes emerged: the evolution of AI-driven threats, the application of AI in cybersecurity defense, and the technical and organizational challenges associated with AI implementation. Implications: The study highlights the importance of integrating technological innovation, human oversight, and governance frameworks to strengthen cybersecurity resilience. Originality: This review provides a holistic perspective by simultaneously examining AI-enabled threats, defensive applications, and implementation challenges within cybersecurity ecosystems.